Pengaruh Model Pembelajaran Talking Stick Terhadap Kemampuan Berbicara Narasi Siswa Sekolah Dasar - Alsina Raisa Dzakira Robbaniah; Sofyan Iskandar; Indah Nurmahanani (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
Virtually every human being born has the potential to speak. language is the most important means of communication in human life. Talking can is defined as a means expressing (one's thoughts, thoughts, heart) to people another by using spoken language so that the point can be understood other. The study is carried out with a view to seeing just how far the impact will go the talking stick learning model to the ability to speak a student narrative to a student a class of V. the kind of research used by researchers was experimentation with using the design of one group preposttest. The subject of this study is student grade V elementary school. The sample that was examined was a total of 38 V grade students basic. Data collection in this study is done by oral testing by telling stories and an interview. Then it was analyzed using prescript-posttest analysis, and the value n - Gain. Research results show that, average value pretest or moment Before treatment is 58.68 and the average posttest or after granted treatment of 83.29. From the data analysis that's been done With linear regression by 70% and n-gain tests in the medium category. Key words: Indonesian learning, Narrative ability, Model talking stick